HUBUNGAN ANTARA EMPATI DAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN PERILAKU PROPOSIAL KELAS XI SMK NEGERI 3 SALATIGA - Eva Setya Oktaviyanti; Umbu Tagela; Adhi Krisna Maria Agustin (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This study aimed to determine the significance of the relationship between empathy and social support of peers with pro-social behavior in Class XI at SMK Negeri 3 Salatiga. The type of research used is a correlational study to find the close relationship between the Empathy variable (X1) and pro-social behavior and the close relationship of the Peer Social Support variable (X2) with pro-social behavior (Y). Then investigate the relationship between the variables Empathy (X1) and Social Peer Support (X2) with pro-social behavior. The population of the study included the entire class XI of SMK Negeri 3 Salatiga, a total of 462 students. Sample determination in this study used a proportionate stratified random sampling technique to determine the number of samples in each class. To determine the sample, the researcher used an error rate of 5%, so the sample the researcher took was 198 students per department of Class XI. The researcher's data collection technique used a scale with 28 items declaring empathy, 33 items declaring peer social support, and 35 items declaring social behavior, with 5 response alternatives. . The data obtained were then analyzed using Kendall's tau_b technique using the statistical program IBM Statistic SPSS version 25.0. The results of the study showed that there is a significant relationship between empathy and pro-social behavior, as evidenced by obtaining a significance value of 0.000 < 0.05 and an r value = 0.531. In addition, the results of research on social support from peers with pro-social behavior showed a significant relationship of 0.000 < 0.05 and r value = 0.505. Meanwhile, the research results on empathy and social support of peers with pro-social behavior showed a significant relationship with the result r = 0.661.